2016
DOI: 10.1002/aenm.201502143
|View full text |Cite
|
Sign up to set email alerts
|

Operando Lithium Dynamics in the Li‐Rich Layered Oxide Cathode Material via Neutron Diffraction

Abstract: in battery technology have come since its fi rst demonstration, the high energy demands needed to electrify the automotive industry have not yet been met with the current technology. [ 2,3 ] One considerable bottleneck is the cathode energy density. [ 2,3 ] The lithium layered oxides utilize transition metal redox pairs for charge/ discharge compensation during lithium extraction and intercalation offering a theoretical capacity of 270 mAh g −1 for complete lithium extraction. [ 3,4 ] However, practical capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 35 publications
6
95
0
Order By: Relevance
“…These repulsive forces would furthermore be reduced by the reported reversible oxygen redox, 26,32,33 whereby it is conceivable that the creation of vacancies in the transition metal layer during the first activation cycle is responsible for enabling oxygen redox processes. 38 However, increasing the Li 2 MnO 3 content leads to an increased lithium occupation in the transition metal layer in the pristine material 58 that will be extracted during the first activation charge, leading to a destabilization of the surface at increasingly lower SOCs, as was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…These repulsive forces would furthermore be reduced by the reported reversible oxygen redox, 26,32,33 whereby it is conceivable that the creation of vacancies in the transition metal layer during the first activation cycle is responsible for enabling oxygen redox processes. 38 However, increasing the Li 2 MnO 3 content leads to an increased lithium occupation in the transition metal layer in the pristine material 58 that will be extracted during the first activation charge, leading to a destabilization of the surface at increasingly lower SOCs, as was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning of the charge at 4.0 V, we observe a continuous displacement field. At 4.2 V the displacement field has changed only slightly, an expected structural response of the nanoparticle to delithiation 20 . When charged to 4.3 V, before the voltage plateau that signifies oxygen evolution 16 , the displacement field is qualitatively different and shows two singularities characteristic of dislocations.…”
mentioning
confidence: 91%
“…The local composition of cations and their associated interaction turns out to be crucial for voltage stability and lithium diffusion capabilities 12,18,19 . Various stacking sequences of the transition metal (TM) layers have been identified (stacking faults) 18,20 . X-ray and neutron scattering measurements revealed that the layer spacing (c lattice parameter) expands during charge from 14.25 Å to about 14.40 Å with simultaneous contraction of the a-b plane 20 , resulting in significant volume changes and cracking of secondary particles upon the initial charge to 4.5 V 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] NRO materials, however, suffer from various drawbacks, such as a difficult synthesis procedure with Ni 3+ ions, low safety, unwanted side reactions with the electrolyte on the surface, moisture/air sensitivity, and quick capacity fading. [15,16] Although spinel LiMn 2 O 4 exhibits appealing cathode features in terms of material abundance, cost, and safety, its use is hindered by its low capacity and its quick fading during cycling due to decomposition of the electrode-electrolyte interphase associated with Mn 2+ dissolution and Jahn-Teller distortion of Mn 3+ ions. [15,16] Although spinel LiMn 2 O 4 exhibits appealing cathode features in terms of material abundance, cost, and safety, its use is hindered by its low capacity and its quick fading during cycling due to decomposition of the electrode-electrolyte interphase associated with Mn 2+ dissolution and Jahn-Teller distortion of Mn 3+ ions.…”
Section: Introductionmentioning
confidence: 99%